Decolonized Worldmaking: Campus Encampments for Civic Engagement - the SoCal for Palestine Coalition (Radical Teacher, 2024)
Despite university administrators’ stated support for free speech, the violent suppression of peaceful, anti-genocide encampments supporting Palestinian liberation across Southern California campuses has shown otherwise. Global solidarity protests that re-emerged in the spring of 2024 received increasingly negative media coverage. Furthermore, university officials and elected leaders openly criticized and sought to dismantle these encampments. This essay serves as a counter-narrative, contextualizing these SoCal Gaza solidarity encampments as acts of decolonized worldmaking in resistance to genocide and in support of Palestinian liberation. These encampments demanded institutional transparency and divestment from financial ties to Israel and arms manufacturers. We argue for recognizing the historical significance of these movements, akin to the anti-apartheid protests of the 1980s and Vietnam War activism of the 1960s. We hope this work contributes meaningfully to the ongoing discourse and knowledge creation around solidarity movements.